1988
DOI: 10.3109/17453678809148784
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of distal forearm fractures in Danish children

Abstract: We recorded all the distal forearm fractures in inhabitants under 20 years of age in Frederiksborg County, Denmark, throughout 1985. The population at risk was 97,791 persons, and fractures occurred in 269 boys and 205 girls. The peak incidence in girls occurred at ages 10-12 (105 per 10,000) and in boys at ages 12-14 (100 per 10,000). Fractures occurred more often in the autumn than in the spring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 5 publications
6
63
2
4
Order By: Relevance
“…In Malmo, the frequency has increased from 23% in 1975-79 (Landin 1983) to 26%, in our study, due to an increase in fracture rate among girls. Girls now seem to have an activity pattern similar to boys, resulting in an increasing incidence of fractures of the distal radius in girls, which also was found by Kramhoft and Bodtker (1988) in Denmark, where the weather conditions are similar to those in southern Sweden. Bailey et al (1989) noted a correlation between the peak incidence of distal radius fractures and the peak velocity of growth in Canadian children.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In Malmo, the frequency has increased from 23% in 1975-79 (Landin 1983) to 26%, in our study, due to an increase in fracture rate among girls. Girls now seem to have an activity pattern similar to boys, resulting in an increasing incidence of fractures of the distal radius in girls, which also was found by Kramhoft and Bodtker (1988) in Denmark, where the weather conditions are similar to those in southern Sweden. Bailey et al (1989) noted a correlation between the peak incidence of distal radius fractures and the peak velocity of growth in Canadian children.…”
Section: Discussionmentioning
confidence: 57%
“…A fracture incidence similar to that in Malmo for [1975][1976][1977][1978][1979] was found in Nottingham children in 1981 (Worlock and Stower 1986). A higher rate of distal forearm fractures than in Landin's findings 1975Landin's findings -1979 was reported by Kramhoft and Bodtker (1988) in Danish children during 1985, mainly due to more fractures among girls. We have now determined whether there has been a further increase in the incidence of fractures among children in Malmo.…”
Section: Carl Johan Tiderius' Lennart Landin* and Henrik Duppelmentioning
confidence: 63%
“…Nevertheless, the lower BMD observed in teenagers with late puberty has clinical relevance, because this is a period of high fracture incidence. (20,(31)(32)(33) In our cohort, a 28% increased risk of having had a previous fracture during childhood, adolescence, and young adulthood (up until the age of 24 years) for each year age at PHV increased, was observed.…”
Section: Pubertal Timing and Bmd In Adolescentsmentioning
confidence: 76%
“…Previous studies [1,7,8] have found that the incidence of distal forearm fractures in children reaches a peak at or about the time of the pubertal growth spurt. One explanation for this observation is a transient increase in cortical porosity, resulting from increased bone turnover due to increased calcium demands at the time of greatest longitudinal bone growth [10].…”
Section: Discussionmentioning
confidence: 99%